Effect of Different Potting Mixes on Germination and Vegetative Growth of Sweet Pepper Plant (Capsicum Annum L.) Under Greenhouse Conditions - Rekani, Omar A. O.; Ameen, Hajar A.; Ahmed, Sarwar M. R. (Science Journal of University of Zakho, 2016)
Sweet pepper is a high nutrient demanding vegetable crop. Fertilizer use and management is therefore of highly important to sustain growth and high yield. However, this study aimed to evaluate the effect of using different types of organic fertilizer on germination and vegetative growth of sweet pepper plant, that have bell-shaped (Capsicum annum L), grown in pots culture under greenhouse condition. The study was conducted at the College of Agriculture, Duhok Governorate, Kurdistan region, Iraq during March 15th, 2015, to June 25th, 2015. The treatments that have been compared in this study were: T1 (Control 100% soil); T2 Municipal Solid Waste compost taken from Kashe factory (1:1 V/V); T3 Sheep manure (1:1 V/V); and T4Peat moss (1:1 V/V).The experiment was randomized complete design with three replicate. The parameters that have been measured were: germination percentage, plant height; number of leave per plant; leaf area and plant fresh and dry weight per pot. In most cases all the studied growth parameters were significantly higher in pot treated by peatmoss and sheep manure compared to control and Municipal Solid Waste compost. Germination percentage was also significantly enhanced in treatment amended by peatmoss and sheep manure. Municipal waste compost was significantly reduced the all the plant growth parameter and germination percentage as well. Depending on these results it can be suggested that organic fertilizers particularly peatmoss and sheep manure can be used to enhance growth and productivity in plant pepper. It was also claimed that the amount of municipal waste compost that was used in this experiment might be too high so further study should be conducted with different ratio on the quality of this type of organic fertilizer.